Makna Pesan Politik pada Foto Akun Instagram Anies Baswedan - Gagas Tri Anggoro; Suyanto; Muchid (Jurnal Komunikasi Nusantara, 2022)
This study was motivated by the summons of Anies Baswedan by the authorities due to the permission of the prophet's birthday, demonstrations due to omnibus law, and the decline in Indonesia's democracy index, resulting in an Instagram photo of Anies Baswedan reading the book "How Democracies Die" on his Instagram account. This study aims to determine and analyze the denotation of political messages, connotations of political messages, myths of political messages, and the meaning of political messages contained in the Instagram photo of the Governor of DKI Jakarta Anies Baswedan. This research method uses qualitative methods with semiotic analysis according to Roland Barthes. The results of the study show that: (1) the denotation of political messages contained in the Instagram photo of the Governor of DKI Jakarta Anies Baswedan reading the book "How Democracies Die" is that Muslim leaders finish praying and take the time to read books related to democracy; (2) the connotation of the political message is a leader who wants to invite the public and the government to jointly improve Indonesia's declining democracy index, because a continuous decline in the democracy index can cause democracy to die; (3) the myth of the political message is that there are leaders who tell them there are problems related to Indonesian democracy; (4) the meaning of his political message is an invitation to improve Indonesian democracy, because democracy can die, another meaning is to improve his self-image and increase his electability as a political figure. Abstrak Kajian ini dilatarbelakangi peristiwa pemanggilan Anies Baswedan oleh pihak berwajib akibat izin maulid nabi, adanya peristiwa demonstrasi akibat omnibuslaw, dan adanya penurunan indeks demokrasi Indonesia, sehingga muncul foto InstagramAnies Baswedan membaca buku “How Democracies Die” pada akun Instagram-nya. Penelitian ini bertujuan untuk mengetahui dan menganalisis denotasi pesan politik, konotasi pesan politik, mitos pesan politik, dan makna pesan politik yang terdapat dalam foto Instagram Gubernur DKI Jakarta Anies Baswedan. Metode penelitian ini menggunakan metode kualitatif dengan analisis semiotik menurut Roland Barthes. Hasil penelitianmenunjukkan bahwa: (1) denotasi pesan politik yang terdapat dalam foto Instagram Gubernur DKI Jakarta Anies Baswedan membaca buku “How Democries Die” adalah pemimpin Muslim selesai sholat dan menyempatkan diri untuk membaca buku terkait demokrasi; (2) konotasi pesan politiknya adalah pemimpin yang ingin mengajak khalayak dan pemerintah untuk bersama-sama meningkatkan indeks demokrasi Indonesia yang turun, karena penurunan indeks demokrasi secara terus menerus dapat mengakibatkan demokrasi mati; (3) mitos pesan politiknya adalah ada pemimpin yang memberitahukan ada masalah terkait demokrasi Indonesia; (4) makna pesan politiknya adalah ajakan untuk meningkatkan demokrasi Indonesia, karena demokrasi dapat mati, makna lainnya adalah untuk meningkatkan citra diri beliau dan peningkatan elektibilitasnya sebagai tokoh politik.